Participation of oxidative stress in selected diseases in the light of the latest research - Justyna Fołta; Zuzanna Rzepka; Dorota Małgorzata Wrześniok (Polish Pharmaceutical Society, 2023)
Disturbances in the balance between the production and accumulation of reactive oxygen species and the proper functioning of antioxidant systems are the source of the phenomenon called oxidative stress. In physiological conditions in the human body, the conditions of the aforementioned balance are maintained, however, in pathological conditions related to exposure to reactive oxygen species or also in the course of diseases, cellular homeostasis may be disturbed. The role of oxidative stress in the pathogenesis and course of diseases affecting many organs has been known for many years. Atherosclerosis, arterial hypertension classified as cardiovascular diseases or neurological diseases such as Parkinson's disease and Alzheimer's disease are just some examples of diseases in which the role of oxidative stress has been known for years. The discovery of new technologies, as well as the sometimes not fully understood pathogenesis of many diseases, is the basis for further research on the impact of reactive oxygen species on pathological processes occurring during the development of the disease and phenomena occurring during treatment. At present, numerous studies and clinical experiments are being carried out, the subject of which is related to the influence of reactive oxygen species on the pathogenesis, clinical picture and treatment of various diseases. Due to the fact that neoplastic diseases are expected to become the most common cause of death, the generation of oxidative stress in neoblastic cells may, on the contrary, become the basis of therapy. The purpose of this article is to review the latest scientific reports on the role of oxidative stress in the pathogenesis and course of selected diseases, i.e. neurological diseases (including Parkinson's disease, Alzheimer's disease, multiple sclerosis and Huntington's disease), cardiovascular diseases (including atherosclerosis arteries, arterial and pulmonary hypertension), lifestyle diseases (diabetes and osteoporosis) and cancer, also in the aspect of therapy with compounds that generate oxidative stress.